Association of polymorphisms in genes encoding prothrombotic and cardiovascular risk factors with disease severity in COVID‐19 patients: A pilot study. Issue 8 (21st April 2022) - Lapić, Ivana; Radić Antolic, Margareta; Horvat, Ivana; Premužić, Vedran; Palić, Jozefina; Rogić, Dunja; Zadro, Renata
Abstract: The present study aimed to assess the association of 16 polymorphisms in genes encoding prothrombotic and cardiovascular risk factors with COVID‐19 disease severity: FV G1691A, FV H1299R, FII G20210A, MTHFR C677T, MTHFR A1298, factor XIII V34L, PAI‐1 4G/5G, EPCR haplotypes (A1/A2/A3), eNOS −786 T > C, eNOS G894T, LTA C804A, ACE I/D, ITGB3 PIA1/A2, ITGA2B Baka/b, β‐Fbg −455 G > A and ApoB R3500Q. The study included 30 patients with severe COVID‐19 and 49 non‐severe COVID‐19 patients. All studied polymorphisms except ITGA2B Baka/b were determined using multilocus genotyping assays CVD StripAssays (ViennaLab Diagnostics), while ITGA2B was genotyped using a real‐time PCR method based on TaqMan technology. A higher frequency of carriers of at least one ITGB3 PIA2 allele was found in severe COVID‐19 patients ( p = 0.009). The distribution of genotypes was significantly different for ß‐Fbg −455 G > A ( p = 0.042), with only three homozygous AA genotypes found among severe COVID‐19 patients. The association with an increased risk for severe COVID‐19 was found for ITGB3, with carriers of at least one ITGB3 PIA2 allele having a 3.5‐fold greater risk of severe COVID‐19 ( p = 0.011). Genotype distribution differences were obtained for the combinations of FV H1299R and FXIII V34L ( p = 0.026), ITGB3 PIA1/A2 and ITGA2B Baka/b ( p = 0.024), and ACE I/D and PAI‐1 4G/5G ( p = 0.046). ITGB3 polymorphism emerged as an independent risk factor for severe COVID‐19 and homozygosity for ß‐Fbg −455 G > A mutation could contribute to disease severity. The combined effect of polymorphisms in genes encoding prothrombotic and cardiovascular risk factors could further contribute to disease severity.